Moderating Role of Alexithymia in Relationship Between Perceived Social Support, Diabetes-Related Quality of Life, and Glycated Hemoglobin in Patients With Type 2 Diabetes - Zeinab Shayeghian; Parisa Amiri; Elnaz Hajati; Safoora Gharibzadeh (Gonabad University of Medical Sciences, 2020)
Background: Diabetes is a complex and chronic disease, i.e. associated with patients' lifestyle and affects their quality of life. The present study examined the role of alexithymia on the relationship between social support, health-related quality of life, and glycated hemoglobin in patients with type 2 diabetes.  Methods: This was an analytical cross-sectional study. The study participants consisted of 100 (60% females) type 2 diabetic out-patients visiting the Labbafinejad Hospital in Tehran City, Iran, between February 2013 and January 2014. Measures of data collection included the multidimensional scale of perceived social support, the diabetes-related quality of life, and alexithymia Scale.  Results: The results of two hierarchical linear regression analyses indicated that alexithymia moderated the relationship between perceived social support, quality of life, alexithymia scale, and HbA1c in patients. To evaluate the moderating role, two hierarchical multiple regression analyses were calculated. The obtained results suggested that alexithymia moderates the relationship between social support, health-related quality of life, and glycated hemoglobin in patients with type 2 diabetes (P>0.001).  Conclusion: The study findings contribute to a better understanding of effective psychosocial factors in the quality of life and HbA1c among patients with diabetes. Therefore, developing psychological interventions is essential for these patients.